Corrosion-resistant high-voltage composite insulator and preparation method thereof

By using raw materials such as alumina powder and titanium dioxide modified fibers, combined with electrospinning and dopamine modification, corrosion-resistant high-pressure composite insulators were prepared, which solved the problem of insulators in acid rain environments and achieved good corrosion resistance and mechanical properties.

CN117198662BActive Publication Date: 2025-03-11JIANGXI LIHUA ELECTRIC PORCELAIN MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310577232.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-03-11
Estimated Expiration
2043-05-22

AI Technical Summary

Technical Problem

Insulators are susceptible to acid rain erosion in a contaminated atmospheric environment, resulting in surface corrosion and damage, affecting their hydrophobic properties, and thus prone to stain flashes.

Method used

Corrosion-resistant high-pressure composite insulators are prepared by raw materials such as alumina powder, titanium dioxide modified fibers, kaolin, zirconia powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talc powder, and the bond strength between fiber and ceramic components is improved through specific preparation methods, including electrospinning and dopamine modification.

Benefits of technology

In the environment of chloride ion corrosion, the insulator has less mass loss and high flexural strength, which shows good corrosion resistance and mechanical properties, improving the durability of the insulator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004240350730000011
    Figure HDA0004240350730000011
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant high-voltage composite insulator, the raw materials of which include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder. After the insulator material prepared by the method of the invention is immersed in a chloride ion corrosion environment, the mass loss is small and the bending strength is high, thereby improving the durability of the insulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulator materials, and in particular to a corrosion-resistant high-voltage composite insulator and a preparation method thereof. Background Art

[0002] As the support for the development of the national economy and the basis of people's daily life, electricity is an indispensable energy source for social production and life. Power outages have a significant impact on daily production and life, especially primary and secondary loads. In severe cases, it will lead to a series of personal accidents and cause significant losses. It is particularly important to prevent power outages and ensure the stable operation of the power system, which is also the fundamental task of the power industry. In the power system, insulators are the most widely used and distributed electrical equipment. They bear the role of mechanical support and electrical insulation of transmission lines and electrical equipment. Their good performance is an important guarantee for the safe and stable operation of the power system. Due to the long-term operation of insulators in a polluted atmospheric environment and the possible erosion of acid rain, salt particles are easily deposited on their surfaces. After being soaked in rain, fog, dew, etc., salt solutions are formed and then corroded on their insulating surfaces, followed by tearing, fading, powdering and other damage phenomena. These damage phenomena affect the hydrophobicity of the insulators, which is specifically manifested as a decrease in their hydrophobicity or even temporary failure, which makes the insulators prone to pollution flashover. Summary of the invention

[0003] To this end, the present invention provides a corrosion-resistant high-voltage composite insulator, the raw materials of which include: alumina powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; the preparation method of the titanium dioxide modified fiber is:

[0004] (1) preparing an ethanol solution of n-butyl titanate, stirring the ethanol solution of n-butyl titanate, and then sequentially adding polyethylene oxide, ammonium chlororhodiumate, cerium nitrate and polyvinyl pyrrolidone to the solution under stirring, and stirring the solution for 30 to 40 minutes after the addition is completed to obtain a spinning precursor mixed solution;

[0005] (2) electrospinning the spinning precursor mixture into a fiber filament, then calcining the fiber filament at 500-550° C. for more than 1 hour, and air-cooling to room temperature to obtain a titanium dioxide-based fiber;

[0006] (3) preparing an aqueous solution of dopamine, dispersing the titanium dioxide-based fibers in the aqueous solution of dopamine, stirring the solution, adding sodium persulfate to the solution during the stirring process, adjusting the pH of the solution to 8.5 with a sodium hydroxide solution after the addition is completed, and then stirring the solution for more than 2 hours, separating the solid and the liquid, washing the solid phase with deionized water, and drying to obtain a once-treated titanium dioxide-based fiber;

[0007] (4) preparing an aqueous solution of sodium fluoride, dispersing the once treated titanium dioxide-based fibers in the aqueous solution of sodium fluoride to form a suspension, keeping the suspension at a constant temperature of 60° C. in a water bath, stirring the suspension for 4 to 5 hours after keeping the temperature, and then air-cooling it to room temperature, separating the solid from the liquid, heating the solid phase to 400° C. and keeping the temperature for more than 3 hours, and air-cooling it to obtain the titanium dioxide modified fibers.

[0008] Furthermore, the raw materials of the composite insulator are calculated by weight as follows: 50 parts of alumina powder; 12-16 parts of titanium dioxide modified fiber; 3-8 parts of kaolin; 10-20 parts of zirconium oxide powder; 2-5 parts of boron trioxide powder; 4-8 parts of calcium oxide powder; 1-2 parts of potassium oxide powder; and 1-3 parts of talc.

[0009] Furthermore, the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talc powder are all sieved powders passing through a 300-mesh sieve.

[0010] Furthermore, in the ethanol solution of n-butyl titanate, the mass percentage of n-butyl titanate is 8% to 10%; the mass ratio of the added mass of polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.03 to 0.04: 0.5 to 0.8: 1 to 2: 1 to 3:10.

[0011] Furthermore, the electrospinning process is as follows: the temperature is 25±3°C, the relative humidity is 40% to 50%, the spinning voltage is 15kV, the spinning precursor mixed liquid injection rate is 1mL / h, the distance between the capillary and the collecting screen is 12cm, and the inner diameter of the spinneret needle is 0.84mm.

[0012] Furthermore, in the aqueous solution of dopamine, the concentration of dopamine is 1.6-2 g / L, the mass ratio of the titanium dioxide-based fibers dispersed in the aqueous solution of dopamine is titanium dioxide-based fibers / aqueous solution of dopamine = 1:20; the mass ratio of the added sodium persulfate is sodium persulfate:dopamine = 6-8:1; the mass percentage of sodium hydroxide in the sodium hydroxide solution is 10%, and the solvent is water.

[0013] Furthermore, in the aqueous solution of sodium fluoride, the concentration of sodium fluoride is 1-2 g / 100 mL, and the solvent is water; the mass ratio of the once-treated titanium dioxide-based fiber dispersed in the aqueous solution of sodium fluoride is once-treated titanium dioxide-based fiber / sodium fluoride aqueous solution = 1:30.

[0014] The preparation method of the composite insulator is as follows:

[0015] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0016] Step 2: pour the slurry into a mold and press-form the blank, and dry the blank at 35° C. for 1 hour to obtain a green blank;

[0017] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h; then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6-7h; then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air cooling it to room temperature to obtain the composite insulator.

[0018] The beneficial effect of the present invention is that after the insulator material prepared by the method of the present invention is immersed in a chloride ion corrosion environment, the mass loss is small and the bending strength is high. It can be seen that the insulator prepared by the present invention has good corrosion resistance and mechanical properties, and the durability of the insulator is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The following is a comparison chart of the corrosion resistance and flexural strength of the test specimens prepared by the methods described in each embodiment and comparative example. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments.

[0021] Example 1

[0022] A corrosion-resistant high-voltage composite insulator, the raw materials include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; the raw materials are calculated by weight as follows: 50 parts of aluminum oxide powder; 12 parts of titanium dioxide modified fiber; 3 parts of kaolin; 10 parts of zirconium oxide powder; 2 parts of boron trioxide powder; 4 parts of calcium oxide powder; 1 part of potassium oxide powder; 1 part of talcum powder. The aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders passing through a 300-mesh sieve. The preparation method of the titanium dioxide modified fiber is:

[0023] (1) preparing an ethanol solution of n-butyl titanate, wherein the mass percentage of n-butyl titanate in the ethanol solution of n-butyl titanate is 8%; stirring the ethanol solution of n-butyl titanate at 50 r / min, and then adding polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the solution in sequence under stirring, and continuing to stir the solution at 50 r / min for 30 minutes after the addition is completed, to obtain a spinning precursor mixed solution; wherein the mass ratio of the polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone added to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.03:0.5:1:1:10;

[0024] (2) The spinning precursor mixture is electrospinned into a fiber filament, and then the fiber filament is calcined at 530° C. for 1 hour, and air-cooled to room temperature to obtain a titanium dioxide-based fiber; the electrospinning process is as follows: the temperature is 25±3° C., the relative humidity is 50%, the spinning voltage is 15 kV, the spinning precursor mixture injection speed is 1 mL / h, the distance between the capillary and the collecting screen is 12 cm, and the inner diameter of the spinneret needle is 0.84 mm;

[0025] (3) preparing an aqueous solution of dopamine, dispersing the titanium dioxide-based fibers in the aqueous solution of dopamine, wherein the concentration of dopamine in the aqueous solution of dopamine is 1.6 g / L, and the mass ratio of the titanium dioxide-based fibers dispersed in the aqueous solution of dopamine is titanium dioxide-based fibers / aqueous solution of dopamine = 1:20; stirring the solution at 30 r / min, adding sodium persulfate to the solution during stirring, wherein the mass of the sodium persulfate added is the mass ratio of dopamine in the solution, and the mass ratio of sodium persulfate to dopamine is 6:1; after the addition is completed, adjusting the pH of the solution to 8.5 with a sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 10%, and the solvent is water; then stirring the solution at 30 r / min for 2 h, separating the solid and the liquid, washing the solid phase with deionized water, and drying to obtain a once-treated titanium dioxide-based fiber;

[0026] (4) preparing an aqueous solution of sodium fluoride, wherein the concentration of sodium fluoride in the aqueous solution of sodium fluoride is 1 g / 100 mL, and the solvent is water; dispersing the once-treated titanium dioxide-based fiber in the aqueous solution of sodium fluoride to form a suspension, wherein the mass ratio of the once-treated titanium dioxide-based fiber dispersed in the aqueous solution of sodium fluoride is once-treated titanium dioxide-based fiber / sodium fluoride aqueous solution = 1:30; keeping the suspension at a constant temperature of 60° C. in a water bath, stirring the suspension at 30 r / min for 4 h after keeping the suspension, and then air-cooling to room temperature, separating the solid from the liquid, heating the solid phase to 400° C. and keeping the suspension for 3 h, and air-cooling to obtain the titanium dioxide modified fiber.

[0027] The preparation method of the composite insulator is as follows:

[0028] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0029] Step 2: pour the slurry into a mold and press-form the blank, and air-dry the blank at 35° C. for 1 hour to obtain an insulator blank and a test sample blank;

[0030] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h, then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6h, then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air cooling it to room temperature to obtain the composite insulator and the test sample of this embodiment.

[0031] Example 2

[0032] A corrosion-resistant high-voltage composite insulator, the raw materials include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; each raw material is calculated by weight: 50 parts of aluminum oxide powder; 14 parts of titanium dioxide modified fiber; 5 parts of kaolin; 14 parts of zirconium oxide powder; 3 parts of boron trioxide powder; 6 parts of calcium oxide powder; 1 part of potassium oxide powder; 2 parts of talcum powder. The aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders passing through a 300-mesh sieve. The preparation method of the titanium dioxide modified fiber is:

[0033] (1) preparing an ethanol solution of n-butyl titanate, wherein the mass percentage of n-butyl titanate in the ethanol solution of n-butyl titanate is 8%; stirring the ethanol solution of n-butyl titanate at 50 r / min, and then adding polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the solution in sequence under stirring, and continuing to stir the solution at 50 r / min for 30 minutes after the addition is completed, to obtain a spinning precursor mixed solution; wherein the mass ratio of the polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone added to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.03:0.6:1:2:10;

[0034] (2) The spinning precursor mixture is electrospinned into a fiber filament, and then the fiber filament is calcined at 530° C. for 1 hour, and air-cooled to room temperature to obtain a titanium dioxide-based fiber; the electrospinning process is as follows: the temperature is 25±3° C., the relative humidity is 50%, the spinning voltage is 15 kV, the spinning precursor mixture injection speed is 1 mL / h, the distance between the capillary and the collecting screen is 12 cm, and the inner diameter of the spinneret needle is 0.84 mm;

[0035] (3) preparing an aqueous solution of dopamine, dispersing the titanium dioxide-based fibers in the aqueous solution of dopamine, wherein the concentration of dopamine in the aqueous solution of dopamine is 1.8 g / L, and the mass ratio of the titanium dioxide-based fibers dispersed in the aqueous solution of dopamine is titanium dioxide-based fibers / aqueous solution of dopamine = 1:20; stirring the solution at 30 r / min, adding sodium persulfate to the solution during stirring, wherein the mass of the sodium persulfate added is the mass ratio of dopamine in the solution, and the ratio of sodium persulfate to dopamine is 7:1; after the addition is completed, adjusting the pH of the solution to 8.5 with a sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 10%, and the solvent is water; then stirring the solution at 30 r / min for 2 h, separating the solid and the liquid, washing the solid phase with deionized water, and drying to obtain a once-treated titanium dioxide-based fiber;

[0036] (4) preparing an aqueous solution of sodium fluoride, wherein the concentration of sodium fluoride in the aqueous solution of sodium fluoride is 1 g / 100 mL, and the solvent is water; dispersing the once-treated titanium dioxide-based fiber in the aqueous solution of sodium fluoride to form a suspension, wherein the mass ratio of the once-treated titanium dioxide-based fiber dispersed in the aqueous solution of sodium fluoride is once-treated titanium dioxide-based fiber / sodium fluoride aqueous solution = 1:30; keeping the suspension at a constant temperature of 60° C. in a water bath, stirring the suspension at 30 r / min for 4 h after keeping the suspension, and then air-cooling to room temperature, separating the solid from the liquid, heating the solid phase to 400° C. and keeping the suspension for 3 h, and air-cooling to obtain the titanium dioxide modified fiber.

[0037] The preparation method of the composite insulator is as follows:

[0038] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0039] Step 2: pour the slurry into a mold and press-form the blank, and air-dry the blank at 35° C. for 1 hour to obtain an insulator blank and a test sample blank;

[0040] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h, then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6h, then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air cooling it to room temperature to obtain the composite insulator and the test sample of this embodiment.

[0041] Example 3

[0042] A corrosion-resistant high-voltage composite insulator, the raw materials include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; each raw material is calculated by weight: 50 parts of aluminum oxide powder; 14 parts of titanium dioxide modified fiber; 6 parts of kaolin; 17 parts of zirconium oxide powder; 4 parts of boron trioxide powder; 6 parts of calcium oxide powder; 2 parts of potassium oxide powder; 2 parts of talcum powder. The aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders passing through a 300-mesh sieve. The preparation method of the titanium dioxide modified fiber is:

[0043] (1) preparing an ethanol solution of n-butyl titanate, wherein the mass percentage of n-butyl titanate in the ethanol solution of n-butyl titanate is 10%; stirring the ethanol solution of n-butyl titanate at 50 r / min, and then sequentially adding polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the solution under stirring, and continuing to stir the solution at 50 r / min for 30 minutes after the addition is completed, to obtain a spinning precursor mixed solution; wherein the mass ratio of the polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone added to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.04:0.7:2:2:10;

[0044] (2) The spinning precursor mixture is electrospinned into a fiber filament, and then the fiber filament is calcined at 530° C. for 1 hour, and air-cooled to room temperature to obtain a titanium dioxide-based fiber; the electrospinning process is as follows: the temperature is 25±3° C., the relative humidity is 50%, the spinning voltage is 15 kV, the spinning precursor mixture injection speed is 1 mL / h, the distance between the capillary and the collecting screen is 12 cm, and the inner diameter of the spinneret needle is 0.84 mm;

[0045] (3) preparing an aqueous solution of dopamine, dispersing the titanium dioxide-based fibers in the aqueous solution of dopamine, wherein the concentration of dopamine in the aqueous solution of dopamine is 1.8 g / L, and the mass ratio of the titanium dioxide-based fibers dispersed in the aqueous solution of dopamine is titanium dioxide-based fibers / aqueous solution of dopamine = 1:20; stirring the solution at 30 r / min, adding sodium persulfate to the solution during stirring, wherein the mass of the sodium persulfate added is the mass ratio of dopamine in the solution, and the ratio of sodium persulfate to dopamine is 7:1; after the addition is completed, adjusting the pH of the solution to 8.5 with a sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 10%, and the solvent is water; then stirring the solution at 30 r / min for 2 h, separating the solid and the liquid, washing the solid phase with deionized water, and drying to obtain a once-treated titanium dioxide-based fiber;

[0046] (4) preparing an aqueous solution of sodium fluoride, wherein the concentration of sodium fluoride in the aqueous solution of sodium fluoride is 2 g / 100 mL, and the solvent is water; dispersing the once-treated titanium dioxide-based fiber in the aqueous solution of sodium fluoride to form a suspension, wherein the mass ratio of the once-treated titanium dioxide-based fiber dispersed in the aqueous solution of sodium fluoride is once-treated titanium dioxide-based fiber / sodium fluoride aqueous solution = 1:30; keeping the suspension at a constant temperature of 60° C. in a water bath, stirring the suspension at 30 r / min for 4 h after keeping the suspension, and then air-cooling to room temperature, separating the solid from the liquid, heating the solid phase to 400° C. and keeping the suspension for 3 h, and air-cooling to obtain the titanium dioxide modified fiber.

[0047] The preparation method of the composite insulator is as follows:

[0048] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0049] Step 2: pour the slurry into a mold and press-form the blank, and air-dry the blank at 35° C. for 1 hour to obtain an insulator blank and a test sample blank;

[0050] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h, then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6h, then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air cooling it to room temperature to obtain the composite insulator and the test sample of this embodiment.

[0051] Example 4

[0052] A corrosion-resistant high-voltage composite insulator, the raw materials include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; the raw materials are calculated by weight: 50 parts of aluminum oxide powder; 16 parts of titanium dioxide modified fiber; 8 parts of kaolin; 20 parts of zirconium oxide powder; 5 parts of boron trioxide powder; 8 parts of calcium oxide powder; 2 parts of potassium oxide powder; 3 parts of talcum powder. The aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders passing through a 300-mesh sieve. The preparation method of the titanium dioxide modified fiber is:

[0053] (1) preparing an ethanol solution of n-butyl titanate, wherein the mass percentage of n-butyl titanate in the ethanol solution of n-butyl titanate is 10%; stirring the ethanol solution of n-butyl titanate at 50 r / min, and then adding polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the solution in sequence under stirring, and continuing to stir the solution at 50 r / min for 30 minutes after the addition is completed, to obtain a spinning precursor mixed solution; wherein the mass ratio of the polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone added to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.04:0.8:2:3:10;

[0054] (2) The spinning precursor mixture is electrospinned into a fiber filament, and then the fiber filament is calcined at 530° C. for 1 hour, and air-cooled to room temperature to obtain a titanium dioxide-based fiber; the electrospinning process is as follows: the temperature is 25±3° C., the relative humidity is 50%, the spinning voltage is 15 kV, the spinning precursor mixture injection speed is 1 mL / h, the distance between the capillary and the collecting screen is 12 cm, and the inner diameter of the spinneret needle is 0.84 mm;

[0055] (3) preparing an aqueous solution of dopamine, dispersing the titanium dioxide-based fibers in the aqueous solution of dopamine, wherein the concentration of dopamine in the aqueous solution of dopamine is 2 g / L, and the mass ratio of the titanium dioxide-based fibers dispersed in the aqueous solution of dopamine is titanium dioxide-based fibers / aqueous solution of dopamine = 1:20; stirring the solution at 30 r / min, adding sodium persulfate to the solution during stirring, wherein the mass of the sodium persulfate added is the mass ratio of dopamine in the solution of sodium persulfate: dopamine = 8:1; after the addition is completed, adjusting the pH of the solution to 8.5 with a sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 10%, and the solvent is water; then stirring the solution at 30 r / min for 2 h, separating the solid and the liquid, washing the solid phase with deionized water, and drying to obtain a once-treated titanium dioxide-based fiber;

[0056] (4) preparing an aqueous solution of sodium fluoride, wherein the concentration of sodium fluoride in the aqueous solution of sodium fluoride is 2 g / 100 mL, and the solvent is water; dispersing the once-treated titanium dioxide-based fiber in the aqueous solution of sodium fluoride to form a suspension, wherein the mass ratio of the once-treated titanium dioxide-based fiber dispersed in the aqueous solution of sodium fluoride is once-treated titanium dioxide-based fiber / sodium fluoride aqueous solution = 1:30; keeping the suspension at a constant temperature of 60° C. in a water bath, stirring the suspension at 30 r / min for 4 h after keeping the suspension, and then air-cooling to room temperature, separating the solid from the liquid, heating the solid phase to 400° C. and keeping the suspension for 3 h, and air-cooling to obtain the titanium dioxide modified fiber.

[0057] The preparation method of the composite insulator is as follows:

[0058] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0059] Step 2: pour the slurry into a mold and press-form the blank, and air-dry the blank at 35° C. for 1 hour to obtain an insulator blank and a test sample blank;

[0060] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h, then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6h, then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air cooling it to room temperature to obtain the composite insulator and the test sample of this embodiment.

[0061] Comparative Example 1

[0062] A composite insulator for comparison, the raw materials include: aluminum oxide powder, titanium dioxide fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; the raw materials are calculated by weight: 50 parts of aluminum oxide powder; 14 parts of titanium dioxide fiber; 5 parts of kaolin; 14 parts of zirconium oxide powder; 3 parts of boron trioxide powder; 6 parts of calcium oxide powder; 1 part of potassium oxide powder; 2 parts of talcum powder. The aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve. The preparation method of the titanium dioxide fiber is:

[0063] (1) preparing an ethanol solution of n-butyl titanate, wherein the mass percentage of n-butyl titanate in the ethanol solution of n-butyl titanate is 8%; stirring the ethanol solution of n-butyl titanate at 50 r / min, and then adding polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the solution in sequence under stirring, and continuing to stir the solution at 50 r / min for 30 minutes after the addition is completed, to obtain a spinning precursor mixed solution; wherein the mass ratio of the polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone added to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.03:0.6:1:2:10;

[0064] (2) The spinning precursor mixture is formed into a fiber filament by electrospinning, and then the fiber filament is calcined at 530°C for 1 hour, and air-cooled to room temperature to obtain the titanium dioxide fiber described in this comparative example; the electrospinning process is: the temperature is 25±3°C, the relative humidity is 50%, the spinning voltage is 15kV, the injection speed of the spinning precursor mixture is 1mL / h, the distance between the capillary and the collecting screen is 12cm, and the inner diameter of the spinneret needle is 0.84mm.

[0065] The preparation method of the composite insulator is as follows:

[0066] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0067] Step 2: pour the slurry into a mold and press-form the blank, and air-dry the blank at 35° C. for 1 hour to obtain an insulator blank and a test sample blank;

[0068] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h, then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6h, then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air-cooling it to room temperature to obtain the composite insulator and the test sample of this comparative example.

[0069] Comparative Example 2

[0070] A composite insulator for comparison, the raw materials include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; the raw materials are calculated by weight: 50 parts of aluminum oxide powder; 14 parts of titanium dioxide modified fiber; 5 parts of kaolin; 14 parts of zirconium oxide powder; 3 parts of boron trioxide powder; 6 parts of calcium oxide powder; 1 part of potassium oxide powder; 2 parts of talcum powder. The aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders passing through a 300-mesh sieve. The preparation method of the titanium dioxide modified fiber is:

[0071] (1) preparing an ethanol solution of n-butyl titanate, wherein the mass percentage of n-butyl titanate in the ethanol solution of n-butyl titanate is 8%; stirring the ethanol solution of n-butyl titanate at 50 r / min, and then adding polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the solution in sequence under stirring, and continuing to stir the solution at 50 r / min for 30 minutes after the addition is completed, to obtain a spinning precursor mixed solution; wherein the mass ratio of the polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone added to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.03:0.6:1:2:10;

[0072] (2) The spinning precursor mixture is electrospinned into a fiber filament, and then the fiber filament is calcined at 530° C. for 1 hour, and air-cooled to room temperature to obtain a titanium dioxide-based fiber; the electrospinning process is as follows: the temperature is 25±3° C., the relative humidity is 50%, the spinning voltage is 15 kV, the spinning precursor mixture injection speed is 1 mL / h, the distance between the capillary and the collecting screen is 12 cm, and the inner diameter of the spinneret needle is 0.84 mm;

[0073] (3) preparing an aqueous solution of sodium fluoride, wherein the concentration of sodium fluoride in the aqueous solution of sodium fluoride is 1 g / 100 mL, and the solvent is water; dispersing the titanium dioxide-based fiber in the aqueous solution of sodium fluoride to form a suspension, wherein the mass ratio of the titanium dioxide-based fiber dispersed in the aqueous solution of sodium fluoride is titanium dioxide-based fiber / aqueous solution of sodium fluoride = 1:30; keeping the suspension at a constant temperature of 60° C. in a water bath, stirring the suspension at 30 r / min for 4 h after keeping the suspension, and then air-cooling to room temperature, separating the solid from the liquid, heating the solid phase to 400° C. and keeping the suspension for 3 h, and air-cooling to obtain the titanium dioxide modified fiber described in this comparative example.

[0074] The preparation method of the composite insulator is as follows:

[0075] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0076] Step 2: pour the slurry into a mold and press-form the blank, and air-dry the blank at 35° C. for 1 hour to obtain an insulator blank and a test sample blank;

[0077] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h, then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6h, then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air-cooling it to room temperature to obtain the composite insulator and the test sample of this comparative example.

[0078] Comparative Example 3

[0079] A composite insulator for comparison, the raw materials include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; the raw materials are calculated by weight: 50 parts of aluminum oxide powder; 14 parts of titanium dioxide modified fiber; 5 parts of kaolin; 14 parts of zirconium oxide powder; 3 parts of boron trioxide powder; 6 parts of calcium oxide powder; 1 part of potassium oxide powder; 2 parts of talcum powder. The aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders passing through a 300-mesh sieve. The preparation method of the titanium dioxide modified fiber is:

[0080] (1) preparing an ethanol solution of n-butyl titanate, wherein the mass percentage of n-butyl titanate in the ethanol solution of n-butyl titanate is 8%; stirring the ethanol solution of n-butyl titanate at 50 r / min, and then adding polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the solution in sequence under stirring, and continuing to stir the solution at 50 r / min for 30 minutes after the addition is completed, to obtain a spinning precursor mixed solution; wherein the mass ratio of the polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone added to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.03:0.6:1:2:10;

[0081] (2) The spinning precursor mixture is electrospinned into a fiber filament, and then the fiber filament is calcined at 530° C. for 1 hour, and air-cooled to room temperature to obtain a titanium dioxide-based fiber; the electrospinning process is as follows: the temperature is 25±3° C., the relative humidity is 50%, the spinning voltage is 15 kV, the spinning precursor mixture injection speed is 1 mL / h, the distance between the capillary and the collecting screen is 12 cm, and the inner diameter of the spinneret needle is 0.84 mm;

[0082] (3) preparing an aqueous solution of dopamine, dispersing the titanium dioxide-based fibers in the aqueous solution of dopamine, wherein the concentration of dopamine in the aqueous solution of dopamine is 1.8 g / L, and the mass ratio of the titanium dioxide-based fibers dispersed in the aqueous solution of dopamine is titanium dioxide-based fibers / aqueous solution of dopamine = 1:20; stirring the solution at 30 r / min, and adding sodium persulfate to the solution during stirring, wherein the mass of sodium persulfate added is the mass ratio of dopamine in the solution is sodium persulfate:dopamine = 7:1; after the addition is completed, adjusting the pH of the solution to 8.5 with a sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the sodium hydroxide solution is 10%, and the solvent is water; then stirring the solution at 30 r / min for 2 h, separating the solid and the liquid, washing the solid phase with deionized water, and drying to obtain the titanium dioxide modified fiber of this comparative example.

[0083] The preparation method of the composite insulator is as follows:

[0084] Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; mixing each raw material uniformly to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry;

[0085] Step 2: pour the slurry into a mold and press-form the blank, and air-dry the blank at 35° C. for 1 hour to obtain an insulator blank and a test sample blank;

[0086] Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h, then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6h, then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air-cooling it to room temperature to obtain the composite insulator and the test sample of this comparative example.

[0087] Example 5

[0088] The bending strength and corrosion resistance of the test samples prepared by the methods described in the above embodiments and comparative examples were tested respectively, wherein the corrosion resistance was characterized by a chloride ion immersion test, and the test method was as follows: a sodium chloride aqueous solution with a solute mass percentage of 3.5% was prepared as a corrosive solution, and the mass of the test sample before immersion was weighed m0, and then the entire test sample was immersed (solid-liquid mass ratio was solid / liquid = 1:50) in the sodium chloride aqueous solution, and after immersion at room temperature for 30 days, the immersed sample was washed 3 times in deionized water with an ultrasonic cleaner to remove the residual solution on the surface of the sample, and then dried in an 80°C oven for 2h, and the mass of the test sample was tested after air cooling to room temperature. The mass loss before and after corrosion was calculated △m = m0-m1. The results are as follows Figure 1 The bending strength was measured by a tensile tester. The test parameters of each sample were set exactly the same, and the pressure head pressing speed was set to 0.5mm / min. The results are shown in Figure 1 shown.

[0089] Depend on Figure 1 It can be seen that the insulator material prepared by the method of the present invention has less mass loss and higher bending strength after being immersed in a chloride ion corrosion environment. It can be seen that the insulator prepared by the present invention has good corrosion resistance and mechanical properties, and improves the durability of the insulator. Comparative Example 2 and each comparative example show that the present invention can further improve the corrosion resistance and strength of alumina composite ceramics by adding titanium dioxide modified fibers. This is mainly because the titanium dioxide fiber itself has a second phase strengthening effect on the ceramic matrix, and after the fiber is modified by dopamine and treated with fluorine ions, a macromolecular group is formed on the fiber surface, and fluorine is adsorbed, which reduces the aggregation of the fibers and improves the bonding strength between the fibers and other components of the ceramic. The addition of fluorine can improve the bonding phenomenon of alumina particles during the sintering process on the one hand, and accelerate the formation of crystal nuclei during the phase transformation of alumina on the other hand, and increase the phase transformation speed, thereby reducing the particle size of the stable phase alumina, improving the strength and density of the material, and reducing the erosion rate of chloride ions.

[0090] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A corrosion-resistant high-voltage composite insulator, characterized in that: The raw materials include: aluminum oxide powder, titanium dioxide modified fiber, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder; the raw materials of the composite insulator are calculated by weight as follows: 50 parts of aluminum oxide powder; 12-16 parts of titanium dioxide modified fiber; 3-8 parts of kaolin; 10-20 parts of zirconium oxide powder; 2-5 parts of boron trioxide powder; 4-8 parts of calcium oxide powder; 1-2 parts of potassium oxide powder; 1-3 parts of talcum powder; wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders passing through a 300-mesh sieve; the preparation method of the titanium dioxide modified fiber is: (1) preparing an ethanol solution of n-butyl titanate, stirring the ethanol solution of n-butyl titanate, and then sequentially adding polyethylene oxide, ammonium chlororhodiumate, cerium nitrate and polyvinyl pyrrolidone to the solution under stirring, and stirring the solution for 30 to 40 minutes after the addition is completed to obtain a spinning precursor mixed solution; (2) electrospinning the spinning precursor mixture into a fiber filament, then calcining the fiber filament at 500-550° C. for more than 1 hour, and air-cooling to room temperature to obtain a titanium dioxide-based fiber; (3) preparing an aqueous solution of dopamine, dispersing the titanium dioxide-based fibers in the aqueous solution of dopamine, stirring the solution, adding sodium persulfate to the solution during the stirring process, adjusting the pH of the solution to 8.5 with a sodium hydroxide solution after the addition is completed, and then stirring the solution for more than 2 hours, separating the solid and the liquid, washing the solid phase with deionized water, and drying to obtain a once-treated titanium dioxide-based fiber; (4) preparing an aqueous solution of sodium fluoride, dispersing the once treated titanium dioxide-based fiber in the aqueous solution of sodium fluoride to form a suspension, keeping the suspension at a constant temperature of 60° C. in a water bath, stirring the suspension for 4 to 5 hours after keeping the temperature, and then air-cooling it to room temperature, separating the solid from the liquid, heating the solid phase to 400° C. and keeping the temperature for more than 3 hours, and air-cooling it to obtain the titanium dioxide modified fiber.

2. A corrosion-resistant high-voltage composite insulator according to claim 1, characterized in that: In the ethanol solution of n-butyl titanate, the mass percentage of n-butyl titanate is 8% to 10%; the mass ratio of the added mass of polyethylene oxide, ammonium chlororhodate, cerium nitrate and polyvinyl pyrrolidone to the mass ratio of the n-butyl titanate in the solution is polyethylene oxide: ammonium chlororhodate: cerium nitrate: polyvinyl pyrrolidone: n-butyl titanate = 0.03 to 0.04: 0.5 to 0.8: 1 to 2: 1 to 3:

10.

3. The corrosion-resistant high-voltage composite insulator according to claim 1, characterized in that: The electrospinning process is as follows: the temperature is 25±3°C, the relative humidity is 40% to 50%, the spinning voltage is 15kV, the spinning precursor mixed liquid injection speed is 1mL / h, the distance between the capillary and the collecting screen is 12cm, and the inner diameter of the spinneret needle is 0.84mm.

4. The corrosion-resistant high-voltage composite insulator according to claim 1, characterized in that: In the aqueous solution of dopamine, the concentration of dopamine is 1.6-2 g / L, the mass ratio of the titanium dioxide-based fibers dispersed in the aqueous solution of dopamine is titanium dioxide-based fibers / aqueous solution of dopamine = 1:20; the mass ratio of the added sodium persulfate is sodium persulfate:dopamine = 6-8:1; the mass percentage of sodium hydroxide in the sodium hydroxide solution is 10%, and the solvent is water.

5. The corrosion-resistant high-voltage composite insulator according to claim 1, characterized in that: In the aqueous solution of sodium fluoride, the concentration of sodium fluoride is 1-2 g / 100 mL, and the solvent is water; the mass ratio of the once treated titanium dioxide-based fiber dispersed in the aqueous solution of sodium fluoride is once treated titanium dioxide-based fiber / the aqueous solution of sodium fluoride=1:

30.

6. The method for preparing a corrosion-resistant high-voltage composite insulator according to claim 1, characterized in that: The method steps are: Step 1, weighing each raw material component according to the weight proportion, wherein the aluminum oxide powder, kaolin, zirconium oxide powder, boron trioxide powder, calcium oxide powder, potassium oxide powder and talcum powder are all sieved powders through a 300-mesh sieve; uniformly mixing the raw materials to obtain a powder material, and adding 30% of the total weight of pure water to the powder material to prepare a slurry; Step 2: pour the slurry into a mold and press-form the blank, and dry the blank at 35° C. for 1 hour to obtain a green blank; Step 3, placing the green body into a kiln, heating it to 600°C at a rate of 20°C / h, and keeping it warm for 2h; then heating it to 1200°C at a rate of 10°C / h, and keeping it warm for 2h; then heating it to 1500°C at a rate of 10°C / h, and keeping it warm for 1h; then heating it to 1680°C at a rate of 10°C / h, and keeping it warm for 6-7h; then cooling it to 600°C at a rate of 10°C / h, keeping it warm for 30min, then cooling it to 250°C at a rate of 20°C / h, and then air cooling it to room temperature to obtain the composite insulator.

Citation Information

Patent Citations

  • Corrosion-resistant ceramic-based composite material and preparation method thereof

    CN108821788A

  • Sulfur-carrying porous titanium dioxide / carbon nano composite fiber as well as preparation and application thereof

    CN109817930A